Mechanisms of Antitumour Activity of 3,19-(2 Bromobenzylidene) Andrographolide (SRJ09) - Lim, Siang Hui (2007)
To date, most of the clinical cytotoxic anticancer drugs target all rapidly dividing cells and are non-selective in their mechanism of action by disrupting essential components that are crucial to both malignant and normal cells. Hence, the search for more effective and selective anticancer drugs is currently being researched actively involving the various entities of the drug discovery programme. We at UPM have shown that andrographolide (AGP), a compound isolated from a local herb, Andrographis paniculata, to have anticancer activity in vitro and in vivo. In order to improve the antitumour properties of AGP, semi-synthetic derivatives of this compound were synthesised in our laboratory, with the aim of identifying the most promising anticancer compound among the AGP derivatives and to elucidate the mechanism(s) of action of the compound. The in vitro antitumour study showed that 3,19-(2-bromobenzylidene)andrographolide (SR09) displayed better antitumour activity when compared with AGP and other derivatives namely 3,19-(2- chlorobenzylidene)andrographolide (SRJ11) and 3,19-(3-chloro-4- fluorobenzylidene) andrographolide (SRJ23). The antitumour activity of AGP, SRJ09, SRJ11 and SRJ23 was shown to be not compromised by P-glycoprotein activities in MES-SA Dx5 multidrug resistant cell line. The time-course study revealed SRJ09 had a rapid acting interval compared with AGP. SRJ09 was previously shown to induce G1-phase cell cycle arrest and in this study the effect was shown attributed to increased of p21 (CDK inhibitor) expression without affecting the expression of cyclin D1. Apoptosis was the main mode of cell death induced by SRJ09 and was p53 and bcl-2 independent, which might suggest that SRJ09 act through the extrinsic apoptotic pathway. A simple pharmacokinetic study was performed in Balb/c for the purpose of dose selection for in vivo study revealed that SRJ09 had a relatively short half-life but was able to reach in vitro cytotoxic concentration range. In a subsequent in vivo antitumour study, SRJ09 delayed quadruple tumour growth by 4 day in HCT-116 colon cancer xenografted mice treated with 400 mg/kg SRJ09 (q4d×3) when compared with control. In conclusion, SRJ09 have been proven as a lead anticancer agent given to its ability to induce in vitro cell cycle arrest and apoptosis and to have in vivo antitumour activity. Therefore, further studies in improving the anticancer properties of SRJ09 by chemical modification will be advantageous.